2011
DOI: 10.1128/iai.05418-11
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin with Low Hemolytic Activity Confers an Early Growth Advantage to Streptococcus pneumoniae in the Blood

Abstract: Streptococcus pneumoniae is a leading cause of human diseases such as pneumonia, bacteremia, meningitis, and otitis media. Pneumolysin (Ply) is an important virulence factor of S. pneumoniae and a promising future vaccine target. However, the expansion of clones carrying ply alleles with reduced hemolytic activity has been observed in serotypes associated with outbreaks of invasive disease and includes an allele identified in a highly virulent serotype 1 isolate (ply4496). The virulence of Ply-deficient and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…These truncated proteins consisted of domains 1-3 of Ply (PlyL) and domains 1-3 of Ply306 (PlyL306), as well as domain 4 of Ply (PlyS) and domain 4 of PlyL460D (PlySL460D). PlyS and domain 4 of Ply306 share 100% amino acid sequence identity, and PlyL and domains 1-3 of PlyL460D share 100% amino acid sequence identity (21). It was found that PlyS bound to both LeX and sLeX, whereas the PlySL460D mutant, PlyL, and PlyL306 showed no binding to LeX or sLeX.…”
Section: Resultsmentioning
confidence: 87%
“…These truncated proteins consisted of domains 1-3 of Ply (PlyL) and domains 1-3 of Ply306 (PlyL306), as well as domain 4 of Ply (PlyS) and domain 4 of PlyL460D (PlySL460D). PlyS and domain 4 of Ply306 share 100% amino acid sequence identity, and PlyL and domains 1-3 of PlyL460D share 100% amino acid sequence identity (21). It was found that PlyS bound to both LeX and sLeX, whereas the PlySL460D mutant, PlyL, and PlyL306 showed no binding to LeX or sLeX.…”
Section: Resultsmentioning
confidence: 87%
“…S. pneumoniae serotype 4 bioluminescent strain TIGR4X was grown in chemically defined medium (CϩY) without aeration at 37°C in 5% CO 2 to an optical density at 620 nm (OD 620 ) of 0.4 to 0.5 (54). S. pneumoniae strains D39, 1861, and P9 were grown in serum broth to an OD 600 of 0.18, as previously described (55). S. pneumoniae strains DBL6A, A66.1, and EF3030 were grown in Todd-Hewitt broth to an OD 600 of 0.4, as previously described (42).…”
Section: Methodsmentioning
confidence: 99%
“…We used a PLY-producing clinical isolate of capsular group 19 S. pneumoniae strain EF3030 (6). In selected experiments, an otherwise isogenic PLY-deficient derivate of serotype 19 S. pneumoniae strain EF3030 (EF3030⌬PLY) (19,51) was employed. Bacteria were grown in Todd-Hewitt broth (Oxoid, Basingstoke, United Kingdom) supplemented with 20% fetal calf serum (FCS) (PAA Laboratories, Pasching, Austria) to mid-log phase.…”
Section: Methodsmentioning
confidence: 99%